2020
DOI: 10.1088/1367-2630/abbfce
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing laser–plasma interactions for ion acceleration using particle-in-cell simulations and evolutionary algorithms

Abstract: The development of ultra-intense laser-based sources of high energy ions is an important goal, with a variety of potential applications. One of the barriers to achieving this goal is the need to maximize the conversion efficiency from laser energy to ion energy. We apply a new approach to this problem, in which we use an evolutionary algorithm to optimize conversion efficiency by exploring variations of the target density profile with thousands of one-dimensional particle-in-cell (PIC) simulations. We then com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…where f MX (n 0 , v th0 ) = n 0 exp(−v 2 /v 2 th )/ πv 2 th . By having non-zero ν K only in a small localized region at the boundary, as also described by Strozzi et al (2007), and as shown in figure 8, the particles are absorbed in a fixed Maxwellian, similar to having a thermal boundary condition. This localization is also performed using the hyperbolic tangent parameterization from (A13) but using 1 − g( p, x).…”
Section: Declaration Of Interestsmentioning
confidence: 93%
See 3 more Smart Citations
“…where f MX (n 0 , v th0 ) = n 0 exp(−v 2 /v 2 th )/ πv 2 th . By having non-zero ν K only in a small localized region at the boundary, as also described by Strozzi et al (2007), and as shown in figure 8, the particles are absorbed in a fixed Maxwellian, similar to having a thermal boundary condition. This localization is also performed using the hyperbolic tangent parameterization from (A13) but using 1 − g( p, x).…”
Section: Declaration Of Interestsmentioning
confidence: 93%
“…These nonlinear electrostatic wavepackets are dynamically evolving, finite-length analogues of the well-known, time-independent, periodic Bernstein-Greene-Kruskal (BGK) modes described in Bernstein et al (1957). Simulations of stimulated Raman scattering (SRS) in inertial confinement fusion scenarios show that similar large-amplitude waves, but of finite extent, are generated in the laser-plasma interaction, and that particle trapping is correlated with the transition to the high-reflectivity burst regime of SRS (Strozzi et al 2007;Ellis et al 2012).…”
Section: Discovery Of Long-lived Nonlinear Plasma Wavepacketsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, ML approaches based on neural networks and genetic algorithms require large quantities of data to make accurate predictions, and direct optimisation algorithms can struggle to optimise noisy functions. Bayesian optimisation has been applied to laser-driven electron acceleration experiments [33][34][35], and Bayesian statistics have been used to model laser-driven ion acceleration studies [36], along with other common ML techniques [37,38].…”
Section: Introductionmentioning
confidence: 99%